2018
DOI: 10.12681/mms.15890
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of pelagic tunicates by cetaceans calves in the Mediterranean Sea

Abstract: Gelatinous zooplankton, including jellyfish, ctenophores and pelagic tunicates, constitute fragile marine animals that live in the water column, and represent an important resource for marine food webs through seasonal pulses. Although there is scarce evidence for gelatinous zooplankton occurring in the stomach contents of apex, endothermic predators such as cetaceans, the ecological significance of such observations requires consideration. We herein report the occurrence of pelagic tunicates in the stomach of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Conversely, the broad range of prey consumed by cetaceans encompasses various TS, thus increasing the likelihood of TS overlap with plastic objects. As a result, many odontocetes, including deep divers, although predominantly feeding on cephalopods, also consume fish, crustaceans, and even gelatinous zooplankton of diverse sizes and shapes 26 . This could significantly enhance their susceptibility to acoustically mistake plastics items for potential food sources.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the broad range of prey consumed by cetaceans encompasses various TS, thus increasing the likelihood of TS overlap with plastic objects. As a result, many odontocetes, including deep divers, although predominantly feeding on cephalopods, also consume fish, crustaceans, and even gelatinous zooplankton of diverse sizes and shapes 26 . This could significantly enhance their susceptibility to acoustically mistake plastics items for potential food sources.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, phylogenetic patterns from the present study broadly support the current sub-familial arrangement of pseudaliids infecting cetaceans into the Halocercinae, Pseudaliinae and Stenuriinae (see Measures, 2001 ), of which Halocercinae would be basal. Interestingly, the bulk of pseudaliid diversity, with representatives of all sub-families, occur in the Delphinoidea (i.e., Delphinidae + Phocoenidae + Monodontidae) worldwide ( Measures, 2001 ; Fraija-Fernández et al, 2016 , Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Pseudaliidae are a family of metastrongyloid lungworms that infect the lungs or cranial sinuses of cetaceans worldwide ( Measures, 2001 ; Anderson et al, 2009 ; Fraija-Fernández et al, 2016 ), except for Stenuroides herpestis , which is found in the lungs of the Egyptian mongoose, Herpestis ichneumon ( Gerichter, 1951 ; Blanco et al, 1993 ). Three sub-families, 6 genera and 31 species are currently recognised within this family ( Delyamure 1955 ; Measures, 2001 ; Fraija-Fernández et al, 2016 ; Pool et al, 2020b ): the Pseudaliinae Railliet and Henry, 1909, with the genus Pseudalius Railliet and Henry, 1909 (1 sp. ); the Halocercinae Delyamure, 1955 , with the genus Halocercus Baylis and Daubney, 1925 (13 spp.…”
Section: Introductionmentioning
confidence: 99%
“…The Pseudaliidae are a family of metastrongyloid lungworms almost exclusive to cetaceans, having been reported in ca. 29 odontocete species worldwide (Fraija‐Fernández et al, 2016; Measures, 2001). Despite their name, pseudaliids can be found not only in the lungs, but also in the cranial sinuses, where heavy worm burdens can cause osseous lesions (Measures, 2001).…”
Section: Introductionmentioning
confidence: 99%